Spirituality and Ethics in Surah Al-Fajr: A Comparison of Al-Misbah's and Al-Azhar's Tafsirs - Hartono Hartono; Raiz Anwar; Ahmad Isnaeni; Siti Badiah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the dimensions of spirituality and ethics in Surah Al-Fajr through a comparative study between Tafsir Al-Azhar by Buya Hamka and Tafsir Al-Misbah by M. Quraish Shihab. The main issue raised is how the messages of the Qur'an respond to the moral crisis and modern materialism. Using a qualitative method with a comparative interpretation approach, this study analyzes the interpretations of the two exegetes on key verses concerning divine oaths, the history of previous peoples, trials of sustenance, and the concept of peace of mind. The results show that both exegetes agree that faith is the core response to life's trials and emphasize that Islamic spirituality is inseparable from social responsibility. The fundamental difference lies in their interpretive orientation: Quraish Shihab in Tafsir Al-Misbah emphasizes a rational-contextual approach and linguistic analysis to correct the theological paradigm. Conversely, Buya Hamka in Tafsir Al-Azhar tends to use a moral-social and Sufi-applicative approach linked to inner experience and social reality. This study concludes that the integration of these two approaches provides a solid normative foundation for the formation of public ethics and transformative spirituality in the contemporary era.